What does prayer teach us about God?. Issue 4 (July 2021) - Holmes, Christopher
Using Augustine as a dialogue partner, I consider what prayer teaches us about God and ourselves in relation to God. I argue, primarily, that prayer illuminates the great distinction between creatures and God, enabling us to live into it. Second, I reflect on the elucidating power of prayer with respect to our participation in God. In so doing, I show the 'shaping effect' of metaphysical reflection on the prayers of the faithful.